2012
DOI: 10.5664/jcsm.1928
|View full text |Cite
|
Sign up to set email alerts
|

The AASM Scoring Manual Four Years Later

Abstract: lent and incident blood pressure; 6,7 (2) lower neurocognitive test scores; 8 and (3) automobile crashes due to sleepiness. 9 The respiratory review paper also provided suffi cient evidence for scoring hypopneas which caused as little as ≥ 20% to 30% fall in airfl ow and/or ≥ 2% or ≥ 3% desaturations. [10][11][12] However, the AASM wanted rules for scoring hypopneas which had substantial or excellent interscorer reliability. Interrater reliability (IRR) as it relates to scoring sleep in a PSG measures how clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 72 publications
2
84
1
8
Order By: Relevance
“…Several prior studies that have assessed the association between snoring and HI have found mixed results. 29,30 In the current study, we found that self-reported snoring was not associated with HI, nor did adjustment for self-reported snoring appreciably change the association between SA and HI. In one of the earliest studies of hearing loss among snorers, Prazic 37 reported varying degrees of hearing loss in 17 snorers although this study lacked information on SA.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Several prior studies that have assessed the association between snoring and HI have found mixed results. 29,30 In the current study, we found that self-reported snoring was not associated with HI, nor did adjustment for self-reported snoring appreciably change the association between SA and HI. In one of the earliest studies of hearing loss among snorers, Prazic 37 reported varying degrees of hearing loss in 17 snorers although this study lacked information on SA.…”
mentioning
confidence: 59%
“…We required events to be linked to a ≥ 3% desaturation in accordance with current recommended hypopnea scoring criteria from the American Academy of Sleep Medicine. 28,29 We defined SA as AHI ≥ 15 events/h. SA severity was defined as: mild or no SA (0 ≤ AHI < 15), moderate SA (15 ≤ AHI < 30), and severe SA (AHI ≥ 30).…”
Section: Sleep-related Variablesmentioning
confidence: 99%
“…Grigg-Damberger, in a recent review, 3 noted that there have been few complaints about the new scoring system. Moser and colleagues 4 found signifi cant differences in stage scores with the AASM Manual.…”
mentioning
confidence: 99%
“…Sertrifikalı teknisyenler tarafından 6 kanal elektroensefalografi (F4-M1, C4-M1, O2-M1, F3-M2, C3-M2, O1-M2), elektrookülografi (E1-M2, E2-M2), bilateral tibia ve çene elektromiyografi, elektrokardiyografi, horlama sensörü, solunumsal olayların kaydı için nazal flow, oro-nazal termistör, respiratuvar indüktans pletismografi bağlanarak tüm gece kayıt alındı. Skorlama, sertifikalı uzman hekim tarafından Amerikan Uyku Tıbbı Akademisi (AASM) 2007 ve 2012 kurallarına göre yapıldı (18,19). OUAS hastalık sınıflaması AASM 2014 Uluslararası Uyku Bozuklukları Sınıflaması'na göre yapıldı (20).…”
Section: Gereç Ve Yöntemunclassified